PEMAHAMAN PENGOBATAN BESI PANAS (AL KAY) DALAM PERSPEKTIF HADIS DAN SAINS (STUDI ANALISIS HADIS DALAM KITAB SUNAN ATTIRMIZI) - Dahlia Lubis; Munandar Munandar; Yuriska Sri Daningsih (SHAHIH (Jurnal Ilmu Kewahyuan), 2022)
Al-kay (Heat Iron Treatment) is a treatment that has existed since the time of the Prophet, where the treatment is a traditional medicine that was used in ancient times because there is no treatment with modern tools like today. The existence of the Hadiths that prohibit the treatment of Al-kay hot iron, of course, is a contradiction in the view of the Hadith scholars in particular, where the treatment in this way is prohibited by the Prophet. but he never did the treatment with this method. In this study, the author also examines the treatment in science, where the treatment can be seen as dangerous or not if it is carried out and whether it is very risky for the body. And the al-kay treatment method has developed with tools that resemble al-kay. The author tries to study it by questioning several issues including how the quality of the hadith is, and what are the views of scholars on the traditions regarding the prohibition of hot iron treatment (al-kay). kay) whether it can be used as hujjah or not. The author uses a library research method and the methodological steps that the author takes are the sanad and matan criticism method, this is an attempt to find hadiths about the prohibition of treatment with the al-kay method (hot iron) which The quality is authentic, both in terms of sanad and in terms of maturity and can be used as evidence. Furthermore, the author performs takhrij al-hadith from al-kutub at-tis'ah by using the book of Tahdzib at-Tahdzib and the book of Tahdzib al-Kamal and using the al-Tahdzib application. Maktabah As Shamilah. The data collection method is the documentation method which tries to collect all primary and secondary data. The primary data is included in the Mu'tamar books and also the syarh hadith books. While the secondary data is literature related to discussion of the problem of 'alkay' treatment. As for the Prophet. prohibit the treatment because it is very risky and can damage the outer body skin.